OVERCOMING DRUG CRIMES IN SOCIETY FROM THE PERSPECTIVE OF PANCASILA JUSTICE - Abdul Kholiq; Vincentius Simon Suyanto; Edi Sutikno (UNTAG Law Review, 2025)
Submission:2025-04-21Review:2025-05-17Accepted:2025-05-22Publish: 2025-5-31ABSTRACT: National development aims to create a prosperous, just, and equitable society, both materially and spiritually, based on Pancasila and the 1945 Constitution. Efforts to improve public services include health, narcotics, psychotropics, and other addictive substances. Drug crimes are generally not committed by individuals alone, but rather collectively, even by organized, well-organized, and highly secretive syndicates. Furthermore, drug trafficking is transnational in nature, carried out using sophisticated methods and technology. To combat drug abuse, the government has issued Law No. 5 of 1997 concerning Psychotropics and Law No. 22 of 1997 concerning Narcotics. Law No. 22 of 1997 has been revoked and replaced by Law No. 39 of 2009. General Provisions Article 1 paragraph (1) of Law No. 5 of 1997 concerning Psychotropics states that psychotropics are substances or drugs, whether natural or synthetic, not narcotics, which have psychoactive properties through selective influence on the central nervous system which causes typical changes in mental activity and behavior.Â Keywords: Combat, Criminal Acts, Drug, Pancasila JusticeSubmission:2025-04-21Review:2025-05-17Accepted:2025-05-22Publish: 2025-5-31ABSTRACT: National development aims to create a prosperous, just, and equitable society, both materially and spiritually, based on Pancasila and the 1945 Constitution. Efforts to improve public services include health, narcotics, psychotropics, and other addictive substances. Drug crimes are generally not committed by individuals alone, but rather collectively, even by organized, well-organized, and highly secretive syndicates. Furthermore, drug trafficking is transnational in nature, carried out using sophisticated methods and technology. To combat drug abuse, the government has issued Law No. 5 of 1997 concerning Psychotropics and Law No. 22 of 1997 concerning Narcotics. Law No. 22 of 1997 has been revoked and replaced by Law No. 39 of 2009. General Provisions Article 1 paragraph (1) of Law No. 5 of 1997 concerning Psychotropics states that psychotropics are substances or drugs, whether natural or synthetic, not narcotics, which have psychoactive properties through selective influence on the central nervous system which causes typical changes in mental activity and behavior.Â